Toll-Like Receptor 9 Enhances Bacterial Clearance and Limits Lung Consolidation in Murine Pneumonia Caused by Methicillin-Resistant Staphylococcus aureus - Anne Jan van der Meer; Achmed Achouiti; Arie van der Ende; Aicha Ait Soussan; Sandrine Florquin; Alex de Vos; Sacha S Zeerleder; Tom van der Poll (BMC, 2016)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) is an important pathogen in pneumonia associated with severe lung damage. Tissue injury causes release of damage-associated molecular patterns (DAMPs), which may perpetuate inflammation. DNA has been implicated as a DAMP that activates inflammation through Toll-like receptor 9 (TLR9). The aim of this study was to evaluate the role of TLR9 in MRSA pneumonia. Wild-type (Wt) and TLR9 knockout (tlr9−/−) mice were infected intranasally with MRSA USA300 (BK 11540) (5E7 CFU) and euthanized at 6, 24, 48 or 72 h for analyses. MRSA pneumonia was associated with profound release of cell-free host DNA in the airways, as reflected by increases in nucleosome and DNA levels in bronchoalveolar lavage fluid (BALF), accompanied by transient detection of pathogen DNA in MRSA-free BALF supernatants. In BALF, as compared with Wt mice, tlr9−/− mice showed reduced tumor necrosis factor α and IL-6 levels at 6 h and reduced bacterial clearance at 6 and 24 h postinfection. Furthermore, tlr9−/− mice exhibited a greater influx of neutrophils in BALF and increased lung consolidation at 24 and 48 h. This study demonstrates the release of host- and pathogen-derived TLR9 ligands (DNA) into the alveolar space after infection with MRSA via the airways and suggests that TLR9 has proinflammatory effects during MRSA pneumonia associated with enhanced bacterial clearance and limitation of lung consolidation.